2000
DOI: 10.1016/s0304-3959(00)00304-3
|View full text |Cite
|
Sign up to set email alerts
|

Spinal effect of the cholecystokinin-B receptor antagonist CI-988 on hyperalgesia, allodynia and morphine-induced analgesia in diabetic and mononeuropathic rats

Abstract: Since evidence points to the involvement of cholecystokinin (CCK) in nociception, we examined the effect of intrathecal CI-988, an antagonist of the CCK-B receptors, on mechanical hyperalgesia and allodynia in normal, mononeuropathic and diabetic rats,. Owing to the anti-opioid activity of CCK, it has been suggested that hyperactivity in the spinal CCK system is responsible for the low sensitivity of neuropathic pain to opioids. We therefore also evaluated the effect of the combination of i.t. CI-988 + i.v. mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…CCK-8 is considered to be the strongest endogenous anti-opioid substance [41,42]. At the level of whole-animal behavior or the electrical activities of central painrelated neurons, many data pointed out that CCK-8 can selectively antagonize the analgesic effect of EA or morphine [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…CCK-8 is considered to be the strongest endogenous anti-opioid substance [41,42]. At the level of whole-animal behavior or the electrical activities of central painrelated neurons, many data pointed out that CCK-8 can selectively antagonize the analgesic effect of EA or morphine [16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Opioid treatment of neuropathic pain is often discouraged, because of concerns about ineffectiveness, the potential for the development of tolerance, the risk of addiction, and various side effects. Several clinical studies showed that opioids, particularly morphine, lacked potent analgesic efficacy in neuropathic pain in humans [203]. On the contrary, other studies showed that morphine could be effective in some patients suffering from neuropathic pain.…”
Section: Opioid Analgesia Clinical Studymentioning
confidence: 99%
“…In diabetic rats, CI-988 enhanced the analgesia induced by morphine, 214 and induced antinociceptive effects on mechanical hyperalgesia. 215 The lack of anxiolytic effects of CI-988 in humans has been attributed to its low bioavailability, 210,216 in part due to its high molecular weight. Therefore, to improve the pharmacokinetic profile, the structure of CI-988 was modified with the aim of reducing the molecular weight and improving the aqueous solubility and absorption, maintaining the binding potency and selectivity at CCK 2 receptors.…”
Section: G Dipeptoidsmentioning
confidence: 99%